Trial Production of Surgical Gloves from Irradiated Natural Rubber Latex on Factory Scale - M. Utama; Herwinarni Herwinarni; M. Sumarti; Siswanto Siswanto; Suharyanto Suharyanto; S Ruslim (PPIKSN-BATAN, 2005)
Trial production of surgical gloves from irradiated natural rubber latex at the PT. Laxindo Utama Serang Banten glove factory has been carried out. The variation of heating temperature and leaching time during processing were evaluated. The physical and mechanical properties and the protein allergen respond of surgical gloves using ELISA method were measured. The results showed that the physical and mechanical of surgical gloves such as tensile strength, modulus, and elongation at break arefound to meet the requirements of the ISO or SNI standard for surgical gloves. While the allergic response through clinical tested latex-sensitive protein allergen known as ELISA test is found to be negative.